Effect of sodium glucose cotransporter 2 inhibitor on liver function tests in Japanese patients with non‐alcoholic fatty liver disease and type 2 diabetes mellitus. Issue 10 (7th December 2016) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiroh; Taketani, Hiroyoshi; Ishiba, Hiroshi; Hara, Tasuku; Okajima, Akira; Umemura, Atsushi; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; et al.
Abstract : Aim: No pharmacological therapies have been established for non‐alcoholic fatty liver disease (NAFLD). Sodium glucose cotransporter 2 inhibitor (SGLT2I) was developed for the treatment of adults with type 2 diabetes mellitus (T2DM). The aim of this retrospective study is to evaluate the efficacy of SGLT2I in NAFLD patients with T2DM. Methods: Twenty‐four biopsy‐proven NAFLD patients with T2DM who received SGLT2I for 24 weeks were retrospectively enrolled as the SGLT2I group. Another 21 NAFLD patients with T2DM treated with dipeptidyl peptidase‐4 inhibitor (DPP4I) for 24 weeks were selected as the DPP4I group. Clinical data were evaluated at baseline and at 4, 12, and 24 weeks. Seventeen patients in the SGLT2I group were evaluated by body composition before and after therapy. Results: Not only body weight and hemoglobin A1c but also transaminase activities were significantly decreased in the SGLT2I group. Reductions in transaminase activities were similar between SGLT2I and DPP4I groups. In the SGLT2I group, body mass index and fasting plasma glucose also decreased after the treatment. Conclusion: Sodium glucose cotransporter 2 inhibitor can be a novel promising agent for the treatment for NAFLD patients with T2DM. Prospective randomized controlled trials are warranted to confirm this efficacy of SGLT2I on NAFLD with T2DM.